Novel supersonically solution blown nanofibers from waste PET bottle for PM0.1-2 filtration: From waste to pollution mitigation. (8th November 2021) - Kakoria, Ashish; Chandel, Sheshang Singh; Sinha-Ray, Sumit
Abstract: Air pollution with enhanced concentration of particulate matters (PM0.1-10 ) have worsened from last decade. Although the demand of facemasks has sky-rocketed during current pandemic, the importance of fibrous air filtration unit, as personal protection equipment, was recognized several years ago. In this work, we have developed nanofiber mats from waste plastic bottles (polythyleneterepthalate, PET) by electrospinning (ES) and supersonic solution blowing (SSB) for filtration of PM0.1-2 . The latter could manufacture nanofibers as fine as 1/3rd of former from same polymer concentration via enhanced strain rate. SSB nanofibers, sandwiched between two cotton clothes, demonstrated 99.7% particle filtration efficiency (PFE) for PM2 at air flow rates 80 L per minute (LPM) with 11.56 Pa/cm 2 pressure drop (ΔP) and quality factor (QF) of 0.03 Pa -1 . The finer fibers allowed a transition flow across mat, reducing ΔP, whereas enhanced interaction between fibers and particles along with reduced drag, emphasized diffusion capture of PMs. Porous SSB fiber mat was more hydrophobic than ES fiber mat. Also, a prototype facemask with SSB mat showed PFE at PM0.2 and 80 LPM flow rate mere 4% reduction after 21 days. Such facemask was washable and after 10 cycles of regular handwashing and sun drying it could still retail >99% PFE for PM2 . Graphical abstract: Image 1 Highlights: Supersonically solution blown ultrafine PET nanofibers were fabricated from waste/spent plastic bottles. Such nanofiber-based mats were proven to be highly efficient (∼99%) in capturing various sizes of PMs from 0.1 to 2 μm. Such mats were more breathable than electrospun ones and significantly better than surgical/medical facemask requisite. The solution blown mats were more hydrophobic than electrospun ones, as well more durable in long term usage cycle.